PERAN PESANTREN DR. MUHAMMAD NATSIR DALAM PEMBERDAYAAN KEWIRAUSAHAAN SANTRI DI DESA BATU BAGIRIAK KEC. LEMBAH GUMANTI KAB. SOLOK - Kekanwil Kekanwil (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2019)
Pesantren Dr. Muhammad Natsir with the characteristics of empowering students as preachers and entrepreneurs. The santri are educated to comprehend religion comprehensively and are equipped with entrepreneurial skills. Therefore, the focus of the research reveals the role of foundations and leaders in empowering students' entrepreneurship; and how the potentials, challenges and opportunities that Dr. Pesantren has Muhammad Natsir. The study uses qualitative methods by collecting primary and secondary data through observation, interviews and documentation techniques with people who contribute to empowering the entrepreneurship of students in Dr. pesantren. Muhammad Natsir.The results of this study revealed that the foundation played a role by creating business units and collaborating with various parties. The Boarding School Leaders play a role by creating an entrepreneurship-based curriculum. Potential owned by boarding schools Dr. Muhammad Natsir in the form of human resources (teachers, leaders, students) and natural resources in the form of business units in agriculture, fisheries and services. The challenges and opportunities faced by pesantren are related to marketing problems, financing of entrepreneurial activities and insufficient expertise in the field of entrepreneurship.Keywords: pesantren, empowerment, santri